Three new species of Curcuma L. (Zingiberaceae) from Bangladesh - Rahman, M. Atiqur; Yusuf, M. (Bangladesh Journal of Plant Taxonomy, 2012)
Three new species of the Section Masantha Horan. of the genus Curcuma L. (Zingiberaceae), viz., C. roxburghii Rahman et Yusuf, C. wallichii Rahman et Yusuf and C. wilcockii Rahman et Yusuf from Bangladesh are described and illustrated. These species were collected from the forests of Rangamati, Moulvi Bazar, Sylhet and Tangail districts. Diagnostic morphological characters from closely related taxa are discussed. A key to the Bangladesh species of Section Masantha Horan. is presented. DOI: http://dx.doi.org/10.3329/bjpt.v19i1.10944 Bangladesh J. Plant Taxon. 19(1): 79-84, 2012 (June)